From popular culture to everyday life - Storey, John, 1950- (Routledge, 2014)
"From Popular Culture to Everyday Life presents a critical exploration of the development of everyday life as an object of study in cultural analysis, wherein John Storey addresses the way in which everyday life is beginning to replace popular culture as a primary concept in cultural studies. Storey presents a range of different ways of thinking theoretically about the everyday; from Freudian and Marxist approaches, to chapters exploring topics such as consumption, mediatization and phenomenological sociology. The book concludes, drawing from the previous nine chapters, with notes towards a definition of what everyday life might look like as a pedagogic object of study in cultural studies.This is an ideal introduction to the theories of everyday life for both undergraduate and postgraduate students of cultural studies, communication studies and media studies"--